2020
DOI: 10.1590/1806-9282.66.10.1409
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods for teaching mechanical ventilation in an emergency setting to sixth-year medical students: a randomized trial

Abstract: SUMMARY OBJECTIVE: To determine if there are significant differences between the tutorial, simulation, or clinical-case-based discussion teaching methods regarding the transmission of medical knowledge on mechanical ventilation. METHODS: A randomized, multicenter, open-label controlled trial was carried out using 3 teaching methods on mechanical ventilation: clinical-case-based discussion, simulation, and online tutorial. Voluntary students of the sixth year of medical school from 11 medical colleges answere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…These results were consistent with the ndings of studies by Tallo, Sajjadi, Ramar, and Bayares. The results of Tallo et al's study suggested that ventilator simulation training resulted in better performance of medical students than "discussion-based clinical case methods" and "online distance learning" [20]. The results of Sajjadi et al's study revealed that online simulator training resulted in better performance and greater satisfaction among nursing students in mechanical ventilation [3].…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with the ndings of studies by Tallo, Sajjadi, Ramar, and Bayares. The results of Tallo et al's study suggested that ventilator simulation training resulted in better performance of medical students than "discussion-based clinical case methods" and "online distance learning" [20]. The results of Sajjadi et al's study revealed that online simulator training resulted in better performance and greater satisfaction among nursing students in mechanical ventilation [3].…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Because of the hemodynamic instability of critically ill patients, continuous-use drugs are often necessary; these can contribute to the development of PI by interfering with peripheral blood flow and tissue perfusion. 49,50 The most frequently prescribed drugs were sedatives, analgesics, and vasoactive drugs. Sedative and analgesic drugs are commonly used in intensive care to reduce respiratory discomfort and improve adaptation to IMV.…”
Section: Discussionmentioning
confidence: 99%
“…Although written assessments such as the MCE can be used to assess learning, SBAs require that learners apply knowledge when they operate a mechanical ventilator in a scenario that mimics real clinical scenarios, providing a more complete assessment of competence. Previous studies showed that simulation in MV can provide lasting knowledge and prepare residents to safely manage ventilated patients ( 30 , 39 , 40 ), and SBAs have been successfully used to identify learning gaps and provide remediation ( 30 ).…”
Section: Discussionmentioning
confidence: 99%